Approaching an experimental electron density model of the biologically active trans‐epoxysuccinyl amide group—Substituent effects vs. crystal packing. (24th January 2017) - Shi, Ming W.; Stewart, Scott G.; Sobolev, Alexandre N.; Dittrich, Birger; Schirmeister, Tanja; Luger, Peter; Hesse, Malte; Chen, Yu‐Sheng; Spackman, Peter R.; Spackman, Mark A.; Grabowsky, Simon
Abstract: The trans ‐epoxysuccinyl amide group as a biologically active moiety in cysteine protease inhibitors such as loxistatin acid E64c has been used as a benchmark system for theoretical studies of environmental effects on the electron density of small active ingredients in relation to their biological activity. Here, the synthesis and the electronic properties of the smallest possible active site model compound are reported to close the gap between the unknown experimental electron density of trans ‐epoxysuccinyl amides and the well‐known function of related drugs. Intramolecular substituent effects are separated from intermolecular crystal packing effects on the electron density, which allows us to predict the conditions under which an experimental electron density investigation on trans ‐epoxysuccinyl amides will be possible. In this context, the special importance of the carboxylic acid function in the model compound for both crystal packing and biological activity is revealed through the novel tool of model energy analysis. Abstract : New syntheses, electron‐density determinations and model‐energy analyses of model compounds bearing the biologically relevant trans ‐epoxysuccinyl amide group in comparison with the drugs loxistatin acid (E64c) and loxistatin (E64d) give insight about the varying importance of different functional groups for binding in the enzyme and the crystal.